2015
DOI: 10.1515/aiht-2015-66-2740
|View full text |Cite
|
Sign up to set email alerts
|

Translation of in vitro to in vivo pyridinium oxime potential in tabun poisoning / Translacija učinkovitosti piridinijevih oksima kod trovanja tabunom iz in vitro sustava u in vivo primjenu

Abstract: Even if organophosphorus (OP) nerve agents were banned entirely, their presence would remain a problem as weapons of terror (like in Syria). Oxime antidotes currently used in medical practice still fall short of their therapeutic purpose, as they fail to fully restore the activity of cholinesterases, the main target for OPs. As orphan drugs, these antidotes are tested too seldom for anybody's benefit. Over the last few decades, search for improved reactivators has reached new levels, but the translation of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Hence, an enzyme–reactivator combination, catalytic to the organophosphate hydrolysis, rather than stoichiometric to conjugation, would greatly reduce doses needed for scavenging. The degradation of OPs in whole human blood observed with both oximes 16 and 18 represents a significant improvement compared with some of our previous ex vivo studies, in which any significant scavenging effect was observed only when the blood was supplemented with suitable hAChE mutants or hBChE. Owing to the financial costs of generating such exogenous enzymes, their short circulation time, and the immunity challenges that arise, the design of oximes with an ability to reactivate native AChE and/or BChE effectively provides a much more desirable approach.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hence, an enzyme–reactivator combination, catalytic to the organophosphate hydrolysis, rather than stoichiometric to conjugation, would greatly reduce doses needed for scavenging. The degradation of OPs in whole human blood observed with both oximes 16 and 18 represents a significant improvement compared with some of our previous ex vivo studies, in which any significant scavenging effect was observed only when the blood was supplemented with suitable hAChE mutants or hBChE. Owing to the financial costs of generating such exogenous enzymes, their short circulation time, and the immunity challenges that arise, the design of oximes with an ability to reactivate native AChE and/or BChE effectively provides a much more desirable approach.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous mono‐ and bis‐pyridinium oximes with a quaternary nitrogen atom, analogous to the standard oximes (Figure ), have been synthesised and tested so far . However, due to their permanent positive charge, they do not cross the blood–brain barrier (BBB) efficiently and hence do not reactivate brain AChE . Therefore, in recent years, several research teams have focused their efforts on developing a new generation of AChE reactivators, including uncharged molecules with protonatable groups…”
Section: Introductionmentioning
confidence: 99%
“…Novel reactivators, or recently developed non‐oxime reactivators, while showing generally broad activity towards the phosphorates and phosphonates and potential to penetrate CNS, exhibit limitations toward reactivation of the tabun conjugate . As pyridinium and imidazolium aldoximes, they are not likely to cross the blood–brain barrier rapidly, conferring their antidotal activity only to the peripheral nervous system and not the CNS . As quaternary ammonium compounds, they are likely to be rapidly cleared by the kidneys, similar to other pyridinium aldoximes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, again, using a combined administration regimen of HI-6 and mutant AChE (pretreatment/post-exposure therapy), we observed a significant delay in symptoms of toxicity and time of death. However, the HI-6 antidotal regimen is likely restricted to the peripheral tissues as shown in our recent study with an analog of HI-6 [33]. Nevertheless, we assume that attenuated symptoms such as tremor, breathing, and locomotor disturbances in mice pretreated with mutant and HI-6 reflected an oxime-assisted the catalytic bioscavenging in vivo .…”
Section: Resultsmentioning
confidence: 82%